What Was Tracta? - Perry, Charles (Petits Propos Culinaires, 2024)
Readers of the cookbook of Apicius, the 2nd-4th century compilation from which we get most of our knowledge of Roman cookery, may be puzzled by the word tracta. The best English translation of the book 1 renders tracta as 'pastry', while the best French translation2 makes it 'paste, dough' (pate) and others3 have boldly interpreted it as 'noodles'.